Rayleigh-Bénard Convection in Ferrofluids in the Microgravity Environment (Journal of Scientific Research, 2016)
We have investigated stability of a ferrofluid in microgravity environment. We consider the effect of the spin viscosity, vortex viscosity, and magnetization relaxation. The eigenvalue problem is solved by employing the Chebyshev pseudospectral method and the results are discussed for all three boundary conditions: free-free, rigid-free and rigid-rigid. In the microgravity environment, the ferrofluid is more resilient to convection and, in general, for all boundary conditions requires higher temperature gradient for the threshold of the convection. It is found that a ferrofluid in microgravity environment is more stable, not only as compared to the case when gravity is present, but also in the pure viscous case.